Implementation of Eid Savings Product Promotion at BMT NU Muncar Branch, Banyuwangi - Fitriani, Luluk; Rahmawati, Eva Dwi (proceedings.icesy, 2026)
This research is motivated by the need for appropriate marketing strategies to increase the number of customers for the Simpanan Hari Raya product at KSPPS BMT NU Muncar Branch. The study aims to analyze the implemented promotion strategies. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation studies involving management and customers. The results show that the promotion strategies include direct field outreach, social media utilization, brochure distribution, and personal service. The determining factors for success are public trust, service quality, and information consistency. The findings also reveal that integrating Islamic values such as honesty in promotion strengthens the institution's positive image. It is concluded that implementing a well-planned, communicative, and sharia-value-based promotion strategy can significantly increase customer acquisition and expand the reach of microfinance services at the institution.